Jagung Sebagai Identitas Kultural Masyarakat Kepulauan Babar - Johan Robert Saimima (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this paper is to study identity, especially cultural identity, which is considered important regarding the nature of humans at all times in building their identity throughout the life of the body and identity as a form of social relationship and interaction, where people understand their identity because there are others (others).) and in dealing with these others, there are interactions both carried out based on similarities and differences. Correspondingly, the relationship and interaction with others, each other identifies or defines himself: with whom he is dealing, in what situations they are related, and what motives may arise in the relationship, so that each knows who we are. and who they are. This means that the identity is basically constructed, and the construction is done contextually (the use of symbols), according to the situations and conditions in which and when the relationships and interactions occur. This view of identity is then constructed contextually with certain situations and conditions. Cultural markers that form the boundaries of identity are chosen arbitrarily (arbitrarily). In this connection, the discussion of corn as a community identity in Southwest Maluku, especially in the Babar Islands, shows that corn as a staple food for the people of Southwest Maluku, has many benefits for the body and health. In addition, this paper will also mention a little about the influence of rice, which is recognized as the national food of the Indonesian nation. The method used as a tool to explain this paper is the historical research method with its logical work stages, namely: collecting and managing sources, and utilizing these sources as useful data to explain the existence of maize as a cultural identity of the people in the Babar Islands, as well as being able to use it as food. local content that contributes to the enrichment of local content subjects in contextual-based education in Maluku.